2018
DOI: 10.1073/pnas.1716580115
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated wound healing in mice by on-site production and delivery of CXCL12 by transformed lactic acid bacteria

Abstract: SignificanceChronic wounds comprise a growing clinical problem that represents >3% of the health care budget in industrialized countries. Drug development is hampered by the proteolytic nature of the wounds, which greatly limits drug bioavailability. Here, we present a technology that circumvents this by on-site production and reduced chemokine degradation. Lactobacilli bacteria were transformed into CXCL12-producing vectors to bioengineer the wound microenvironment after topical application. Consequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 43 publications
3
101
0
2
Order By: Relevance
“…41 A recent study showed that a bioengineered L. reuteri with a plasmid encoding CXCL12 accelerated cutaneous wound healing in mouse, while nontransformed L. reuteri delayed wound closure. 42 In the present study, we demonstrated that 43 L. crispatus and its supernatant decreased proinflammatory cytokines and increased IL-10 production by HeLa cells in the presence of Chlamydia trachomatis. 44 These productive effects seem to be related to TLR2 and TLR4.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…41 A recent study showed that a bioengineered L. reuteri with a plasmid encoding CXCL12 accelerated cutaneous wound healing in mouse, while nontransformed L. reuteri delayed wound closure. 42 In the present study, we demonstrated that 43 L. crispatus and its supernatant decreased proinflammatory cytokines and increased IL-10 production by HeLa cells in the presence of Chlamydia trachomatis. 44 These productive effects seem to be related to TLR2 and TLR4.…”
Section: Discussionsupporting
confidence: 53%
“…28,[38][39][40] On the other hand, L. salivarius and L. plantarum inhibited oral epithelial wound healing 41. A recent study showed that a bioengineered L. reuteri with a plasmid encoding CXCL12 accelerated cutaneous wound healing in mouse, while nontransformed L. reuteri delayed wound closure 42. In the present study, we demonstrated thatL.…”
supporting
confidence: 56%
“…Using live probiotic Lactobacillus as a vehicle for prolonged protein delivery to the local environment of the wound shows promising results [79]. Topical application of live Lactobacillus reuteri engineered to express human or mouse CXCL12 has demonstrated rapid wound closure in healthy mice, as well as hyperglycemic and ischemic murine models [80]. In addition to the prolonged delivery of chemokines following application on the wound, Lactobacillus produces lactic acid as a natural by-product of their metabolic pathways and thereby decreases pH in the wound microenvironment.…”
Section: Chemokinesmentioning
confidence: 99%
“…In line with our findings, a recent publication has demonstrated that in situ bioengineered CXCL12 delivery enhances wound healing in different pathological scenarios including murine models of peripheral ischemia and hyperglycemia and wound healing of human skin models. 51 The rationale of using a gain of function approach in the in vivo studies was 2-fold. First, our research on APCs has a translational goal with the ultimate intention to find solutions for the treatment of ischemic disease.…”
Section: Discussionmentioning
confidence: 99%